2021
DOI: 10.3389/fonc.2021.604584
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gut Microbiome Using Explainable Machine Learning Predicts Risk of Diarrhea Associated With Tyrosine Kinase Inhibitor Neratinib: A Pilot Study

Abstract: DummyNeratinib has great efficacy in treating HER2+ breast cancer but is associated with significant gastrointestinal toxicity. The objective of this pilot study was to understand the association of gut microbiome and neratinib-induced diarrhea. Twenty-five patients (age ≥ 60) were enrolled in a phase II trial evaluating safety and tolerability of neratinib in older adults with HER2+ breast cancer (NCT02673398). Fifty stool samples were collected from 11 patients at baseline and during treatment. 16S rRNA anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Pharmacomicrobiomics focuses on the interplay between gut microbiota and drug response through alterations in pharmacokinetics (ie, modification of drug absorption, distribution, metabolism or elimination) or pharmacodynamics (ie, modification of drug targets or biological pathways leading to varying sensitivity to pharmacological effects). 12 Growing evidence has revealed the intimate relationship between the gut microbiota and anticancer treatments, including chemotherapy, 14 radiotherapy, 15 targeted therapy 16 and immunotherapy. 1 Harnessing the microbiota to optimise cancer treatments has become an alternate avenue for personalised medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacomicrobiomics focuses on the interplay between gut microbiota and drug response through alterations in pharmacokinetics (ie, modification of drug absorption, distribution, metabolism or elimination) or pharmacodynamics (ie, modification of drug targets or biological pathways leading to varying sensitivity to pharmacological effects). 12 Growing evidence has revealed the intimate relationship between the gut microbiota and anticancer treatments, including chemotherapy, 14 radiotherapy, 15 targeted therapy 16 and immunotherapy. 1 Harnessing the microbiota to optimise cancer treatments has become an alternate avenue for personalised medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, endoR is flexible: it can be applied to both random forests and gradient boosted trees, which themselves can be applied to both regression and classification tasks involving various types of features (e.g., microbial abundances and metadata). Finally, endoR is substantially more computationally efficient than, for example, SHAP (Supplementary Figure 8 A-D, and G), which is a common approach for ML model interpretation (31, 35, 92, 93).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, a growing number of studies have demonstrated the benefit of leveraging machine learning to differentiate sample classes in microbiome studies. These include predicting the risk of type 2 diabetes (19), diarrhea associated with cancer treatment (20), and liver disease (21) from the gut microbiome. Additionally, when sampling the microbiome from leg skin, explainable AI was able to identify microbial drivers associated with skin hydration, age, and pre/post-menopausal status from the skin microbiome (22).…”
Section: Introductionmentioning
confidence: 99%